The Chemistry Triangle-Based Multimedia to Build A Good Impression: A Design-Based Research - Sausan, Inas; Saputro, Sulistyo; Indriyanti, Nurma Yunita (Universitas Sebelas Maret, 2023)
Science teachers need to pay attention when introducing chemistry to junior high school students hence they don't have low perceptions of chemistry. Multimedia which based on the chemistry triangle can be a solution in helping teachers explains the relationships among macroscopic, sub-microscopic, and symbolic level of chemistry so students can understand the scientific contents better and have a good perceptions. This research aimed to develop a chemistry triangle-based multimedia to build a good impression on junior high school students about chemistry. The design of chemistry triangle-based multimedia was developed through a design-based research (DBR). The participants in the research were three schools of seventh-grade students in Pekalongan Regency, Indonesia. The data were collected through interviews, observations, questionnaires, and tests. The results of this research were in the form of the complete cycles of DBR carried out to produce a chemistry triangle-based multimedia that meets the criteria in helping teachers introduce chemistry in a way that is more easily accepted by students and gives a positive impression about chemistry. This article describes the four phases of the DBR process in the development of chemistry triangle-based multimedia.